Self-reported urinary incontinence in elderly and its associated factors - Alisson Fernandes Bolina; Flávia Aparecida Dias; Nilce Maria de Freitas Santos; Darlene Mara dos Santos Tavares (Universidade Federal do Ceará, 2013)
Household survey, cross-sectional and observational study that aimed to verify the socio-demographic factors and self-reported morbidities associated with urinary incontinence (UI). The research was carried out between August and December 2008 with 2,142 elderly people. We used a semi-structured instrument, and performed a descriptive analysis and logistic regression (p<0.05). Most were female and with income of up to one minimum wage. UI prevailed among those aged 70├80 years, widowed and uneducated; for the group without UI: 60├70 years, married or living with partner and 4├8 years of study. The factors associated with increased chances of presenting UI were: 70├80 years and 80 years and older, no education and obesity. It is important to pay attention to the factors associated with UI in the development of effective actions on health prevention.